The application of iterative interval arithmetic in path-wise test data generation. (October 2015) - Xing, Ying; Gong, Yun-Zhan; Wang, Ya-Wen; Zhang, Xu-Zhou
Abstract: Research of path-wise test data generation is crucial and challenging in the area of software testing, which can be formulated as a constraint satisfaction problem. In our previous research, a look-ahead search method has been proposed as the constraint solver for path-wise test data generation. This paper analytically studies interval arithmetic of the search method in detail, which enforces arc consistency, and introduces the iterative operator to improve it, aiming at detecting infeasible paths as well as shortening generation time. Experiments were conducted to compare the iterative operator with the classical look-ahead operator AC-3, and to compare the test data generation method using the iterative operator with some currently existing methods. Experimental results validate the effectiveness and practical deployment of the proposed iterative method, and demonstrate that it is applicable in engineering.